Intergovernmental Fiscal Relations in the New EU Member States : Consolidating Reforms - Dillinger, William (Washington, DC: World Bank, 2012)
Subnational governments are an important part of the public sector in the EU8 countries. They provide basic public services in both the social sectors (education, health, and social assistance) and in infrastructure (water supply, sewerage and transport). They account for about one-quarter of government spending. This paper includes the following headings: introduction; evaluation criteria; the system ex ante; political and organizational reforms; assignment of functions; revenues; debt controls; directions for further reform; and conclusions.